Anthropology of the Profane - Arpita Roy (Religions, 2025)
Durkheimian anthropology has so insisted on the primacy of the sacred that one scarcely pauses to think on what role the profane may play in the study of religion. This paper examines the cultivation of dead bodies in the Tantric ritual of shav-sadhana to draw out the element of the “profanation of holy objects” operative within religion. Based on ethnographic research among Tantric specialists in rural Bengal, this paper examines how impurity liquidates the distance between the sacred and the profane which opens a window on the role of mundanity in religious rites and beliefs. I begin by portraying the ritual act undertaken by Tantric practitioners in which corpses ensuing from sudden, untimely deaths are mobilized for spiritual advancement. The ritual and its mode of efficacy are evocative for using impure matter to turn the flow of human ideals away from transcendence to ordinary, human ones. This paper concludes with a snapshot of Kaliyuga, the last age of Hindu cosmogony and the most corrupt, to thematize how the profane forms a lure as much as a barrier to religion.